HUBUNGAN NAFSU MAKAN DENGAN KADAR HEMATOKRIT PADA PENDERITA HIPERTENSI - Al Faqih, Aditya Danial; Pranata, Andi Eka; Sya’id, Achmad; Chandra Purnama, Yugi Hari (Prodi Keperawatan Tegal Program Diploma III Poltekkes Kemenkes Semarang, 2025)
Hypertension is one of the chronic non-communicable diseases that contributes significantly to morbidity and mortality in Indonesia. The pathophysiology of hypertension triggers changes in hematocrit levels and increases illness severity, which may lead to anorexia. This study aims to determine the relationship between appetite and hematocrit levels in patients with hypertension. This research employed a correlational design using a cross-sectional approach. A total of 34 hospitalized hypertensive patients participated in the study. Appetite was assessed using the Measure Appetite Questionnaire, and hematocrit levels were obtained through laboratory tests. Data were analyzed using Spearman Rho test. The majority of respondents had low hematocrit levels (58.8%) and good appetite (61.8%). Statistical analysis showed a significant relationship between appetite and hematocrit levels (p = 0.008), with a moderate correlation strength (r = 0.448). Better appetite was associated with higher hematocrit levels. There is a positive correlation between appetite and hematocrit levels in patients with hypertension. Good appetite is positively associated with normal hematocrit levels in hypertensive patients.